Locally advanced pancreatic cancer: a reliable contraindication to resection in the modern era?. Issue 10 (October 2022) - Fromer, Marc W.; Wilson, Khaleel D.; Philips, Prejesh; Egger, Michael E.; Scoggins, Charles R.; McMasters, Kelly M.; Martin, Robert C.G.
Abstract: Background: The aim of this study is to present radiologically designated LAPC found to be resectable upon surgical exploration and evaluate the outcomes of such resections. Methods: Sequential LAPC patients between 2013 and 2019 were staged and underwent resection were included in the analysis of both perioperative and long-term outcomes. Results: Twenty-eight patients with radiologically-designated LAPC underwent surgical resection after chemotherapy with a median follow-up of 31.7 m, 75% underwent pancreaticoduodenectomy. The margin positivity and local recurrence rates were 21.4% and 35.7%, respectively. When compared to the 30 BRPC controls, the LAPC group had a higher rates of an arterial resection (11vs.1; p = 0.002), but the groups were similar with regard to all other preoperative and intraoperative variables (p < 0.05). Perioperative morbidity rates were similar (25.9%vs21.4%; p = 0.53). The LAPC and BRPC groups were also equivalent with respect to median recurrence-free survival (9.0mo; 95%CI 6.3, 11.7vs.8.3mo; 95%CI 5.4, 11.2) and median overall survival (19.9mo; 95%CI 17.0, 22.7 vs. 19.9mo; 95%CI 14.8, 25.1), respectively. Conclusion: Despite a radiologic designation of locally advanced pancreatic cancer, certain subtypes of LAPC warrant surgical exploration provided the operative surgeon is prepared for major arterial and/or venous resection. Pancreatectomy in these patients has acceptable morbidity and oncologic outcomes, similar to patients who are radiologically borderline resectable.